PENGEMBANGAN SOAL AKM NUMERASI BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN NUMERASI PADA SISWA KELAS V SD - Fatma Cristina Wati; Wendri Wiratsiwi (ELENOR: Elementary School Journal, 2024)
Numeracy literacy is the ability of students to understand mathematical concepts in everyday life. The government's effort to improve students' numeracy skills is by implementing the Minimum Competency Assessment which is implemented at the elementary to high school level. However, the results of interviews conducted at SDIT Al Uswah Tuban show that students' numeracy skills are still low due to a lack of practice questions. The questions used are still general, not including local cultural wisdom. Based on this, this study was designed to measure students' numeracy skills and provide insight into the historical heritage in the Kambang Putih Museum Tuban to students through the questions. This research uses the Research and Development (RnD) method with the Tessmer model. The development stages include preliminary stage and formative evaluation stage. The formative evaluation stage consists of expert review, one-to-one, small group, and field test stages. This research produced 15 questions. Based on the test results at each stage, the validity level of the question is 88% which is included in the valid category, the practicality level gets a score of 88% which is included in the practical category, the effectiveness level with a percentage of 76% which is declared effective, and the question is declared reliable because based on Cronbach Alpha analysis it gets a coefficient of 0.60.